Subclinical hypothyroidism and headaches - Carvalho, Marise de Farias Lima; Santo, Pedro Henrique Muniz Falcão do Espírito; Lima, Raphaella Von Sohsten Calabria; Donato, Helena Mello de Godoy (Headache Medicine, 2018)
Introduction: In the last years, many hormonal dysfunctions have been investigated as causes of headache, among them the hypothyroidism. The headache attributed to hypothyroidism is one of the headaches secondary to homeostasis disorders, around one third of hypothyroid patients may refer headache, but a few works have evaluated the prevalence of headache in subclinical hypothyroid patients, a condition traditionally referred as milder and of questionable importance. Objective: The aim of our work was to review the medical literature about the theme subclinical hypothyroidism and headache. Methods: A research has been performed in search sites as PubMed and SciELO for articles related to the theme using the describers “Hypothyroidism”, “subclinical hypothyroidism”, “headache” and “migraine”. Results: Recent studies have helped to clarify the relation between headache and hypothyroidism as real and striking. Considering specifically the subclinical hypothyroidism, it is possible that the impact of the symptom may be equally relevant in this group. The frequency of migraine seems to be higher among subclinical hypothyroid patients when compared to euthyroid individuals, the results, however, are conflicting for the pediatric population. There must be a benefic effect of the subclinical hypothyroidism treatment over the symptom. Conclusion: Headache is a common and relevant symptom among hypothyroid patients. This relation seems to be also present in subclinical hypothyroid patients, more studies are needed to understand the mechanisms and the importance of the treatment in these cases.